Factors Contributing to Diabetes Patients Not Receiving Annual Dilated Eye Examinations†. (October 2013) - Paksin-Hall, Arraya; Dent, Michelle L.; Dong, Frank; Ablah, Elizabeth
Abstract Purpose: Early detection of diabetic eye disease by dilated eye exam can limit potential vision loss from diabetic retinopathy. The purpose of this study was to examine what variables contribute to diabetes patients not receiving annual dilated eye examinations. Methods: This study used national 2009 Behavioral Risk Factor Surveillance System survey data. Variables used in the analysis included sociodemographics, insurance status, mentally unhealthy days, receipt of annual dilated eye exams, insulin dependence, a history of diabetes education classes, timely annual diabetic foot exams, and history of cardiovascular disease. Survey proportions were calculated, and survey logistic regression was performed with the consideration of survey strata and weight to correct for biases. Results: The likelihood of receiving annual dilated eye exams was correlated with eight statistically significant variables. These variables included age category, income level, education level, health insurance status, mentally unhealthy days within the past month, insulin dependence, a history of diabetic education classes, and timeliness of annual diabetic foot examinations. Conclusions: This study provides a snapshot of variables that may have a bearing on diabetes patients seeking annual dilated retinal examinations. Eight variables were statistically significant in affecting the timeliness of diabetic eye examinations. Thus, resolutions for these factors could be implemented for future improvement of comprehensive health care provided to those with diabetes.